Réponses

2013-11-29T12:28:17+01:00
Bonjour

a = (7y - 8)(5y + 4) 
a = 35y² + 28y - 40y - 32
a = 35y² - 12y - 32

b = 3y(4y - 5) - (6 + 2y)(y - 7)
b = (12y² - 15y) - (6y - 42 + 2y² - 14y)
b = 12y² - 15y - 6y + 42 - 2y² + 14y
b = 10y² - 7y + 42


Si y = -2, alors a = 35 * (-2)² - 12 * (-2) - 32
                       a = 35 * 4 + 24 - 32
                       a = 140 + 24 - 32
                       a = 132

Si y = 1, alors b = 10 * 1² - 7 * 1 + 42
                      b = 10 - 7 + 42
                      b = 45
bonjour pourrait tu bien tout detailler comme par exemple le a: 7y-5... etc ne pas dirctement mettre 35y² stp
(7y)*(5y) = 35y², etc...
Meilleure réponse !
2013-11-29T15:00:48+01:00
A= (7y-8)(5y+4)
  =35y²+28y-40y-32
  =35y²-12y-32
b= 3y(4y-5)-(6+2y)(y-7)
  =12y²-15y-(6y-42+2y²-14y)
  =12y²-15y-6y+42-2y²+14y
  =10y²-7y+42
1) y=-2
(7(-2)-8)(5(-2)+4)
(-14-8)(-10+4)
(-22)(-6)=132
2) y=1
3(1)(4(1)-5)-(6+2(1))(1-7)
3(4-5)-(8)(-6)
3(-1)-8(-6)
-3-(-48)=-3+48=45